Islamic Wasatiyyah Teaching in Indonesian Education: An Analysis of the Tasawuf Approach - Gani, A. (Opción, 2019)
The objective of this qualitative study is to focus on the roleplayed by the Wasatiyyah concept in Indonesian Education via theexploratory content analysis method. For this purpose, the studyanalyzed the Tasawuf approach, the Islamic mysticism. As a result theeducational institutions included such principles like good (khayr) andbad (fasad) or just and moderation as part of the Indonesian curricula.In conclusion, it can be concluded that the Wasatiyyah concept appliedin the Indonesian education is in tandem with the Tasawuf approachconsidered as the main element of Islamic epistemology.